ANALYSIS OF THE SALAMDARMA IRRIGATION AREA PERFORMANCE - Oky Fajar Rochman; Saihul Anwar (FAKULTAS TEKNNIK UNIVERSITAS SWADAYA GUNUNG JATI, 2019)
Salamdarma weir is located right in the border area of Indramayu and Subang, belongs to administrative area of Anjatan District, Indramayu Regency. Managed by PT JasaTirta II Section of Patrol. This irrigation netwoork has a total service area of 35871 Ha, the service area includes Subang District and Indramayu District. The existence of Salamdarma irrigation network has an important role for the farmers especially during dry season to support the crops’ growth.In this research to analyze the performance used parameter from Permen No 11/PRT/M/2015 and calculated using Hydrology regulation from KP 01 Irrigation 2013.The analysis result of this research show that 80,9% of structures and 95,1% of canals are in damaged condition with different various level of damage. Based on the calculation and comparison between potential discharge and water requirement, the potential discharge has fulfilled the irrigation water requirement and the comparison. The water requirement is 29890 lt/s and the potential discharge is 64074 lt/s. The human resources in Salamdarma irrigation there is only deficient in the head of branch position of 12%. For POB, PPA, PPS Personel amount has fulfilled the required amount of personel. The Operation and Maintenance budget in Salamdarma Irrigation is increased at 30,112% between 2016 to 2017. Keyword : Irrigation, Salamdarma, Performance, Irrigation water requirement.